PENGARUH PRAPERLAKUAN OVEN TERHADAP AKTIVITAS ANTIOKSIDAN MINYAK KEMIRI (Aleurites moluccana (L.) Willd) DENGAN METODE DPPH (1,1-Diphenyl-2-picrylhydrazyl) - Aldi Budi Riyanta; Akhmad Aniq Barlian; Lenny Novita (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Candlenut (Aleurites moluccana (L.) Willd) is a plant that is efficacious as an alternative to traditional medicine and contains antioxidant compounds that can donate one or more electrons to free radicals, so that free radical reactions can be inhibited. In addition, the candlenut plant has a relatively hig oil content in candlenut seeds, which is around 55-66%. This study aims to determine the effect of oven time at 40℃ on the yield of candlenut oil and antioxidant activity. The method used is that the candlenut seeds are axtracted using a press machine, previously the candlenut seeds have been pretreated in the oven time variations for 1, 3, and 5 minutes at 40℃. The results showed that the highest yield was at a temperature of 40 for 3 minutes, which was to get results with a yield value of 55,83%. In the concentration and probit log data, it was stated that sample 3 with a time of 5 minutes got the best maximum IC50 value of 109,647 µg/mL, with the IC50 value, candlenut oil was classified as an active antioxidant. Based on these results it can be concluded that the use of oven time pretreatment affected the yield and antioxidant activity.